Sodium-Dependent Phosphate Transporter Protein 1 Is Involved in the Active Uptake of Inorganic Phosphate in Nephrocytes of the Kidney and the Translocation of Pi Into the Tubular Epithelial Cells in the Outer Mantle of the Giant Clam, Tridacna squamosa - Ip, Yuen K.; Boo, Mel V.; Poo, Jeslyn S. T.; Wong, Wai P.; Chew, Shit F. (Frontiers in Marine Science, 2021)
Giant clams display light-enhanced Pi absorption, but how the absorbed Pi is translocated to the symbiotic dinoflagellates living extracellularly in a tubular system is unknown. They can accumulate inorganic phosphate (Pi) in the kidney, but the transport mechanism remains enigmatic. Here, we report that sodium-dependent phosphate transporter protein 1-homolog (PiT1-like), which co-transport Na+ and H2PO4−, could participate in these two processes. The complete cDNA coding sequence of PiT1-like obtained from the fluted giant clam, Tridacna squamosa, comprised 1,665 bp and encoded 553 amino acids (59.3 kDa). In the kidney, PiT1-like was localized in the plasma membrane of nephrocytes, and could therefore absorb Pi from the hemolymph. As its gene and protein expression levels were up-regulated in the kidney during illumination, PiT1-like could increase the removal of Pi from the hemolymph during light-enhanced Pi uptake. In the ctenidial epithelial cells, PiT1-like had a basolateral localization and its expression was also light-dependent. It might function mainly in Pi sensing, or absorption of Pi from the hemolymph when Pi becomes limiting. In the outer mantle, PiT1-like was localized in the basolateral membrane of epithelial cells forming the tertiary tubules. It displayed light-enhanced expression levels, indicating that the host could increase the translocation of Pi from the hemolymph into the tubular epithelial cells and subsequently into the luminal fluid to support increased Pi metabolism in the photosynthesizing dinoflagellates. Taken together, the accumulation of Pi in the kidney of giant clams might be unrelated to limiting the availability of Pi to the symbionts.